Recruitment and appointment of academic staff and administrative personnel in selected vocational educational institutions in the Philippines - Kamwangchan, Sunthorn (s.n.], 1972)
The content of this study are grouped into six major parts, namely: a) the difference of the organization and staffing patterns in vocational colleges and schools of arts and trades; b) the provisions of the Magna Carta for Public School Teachers relevant to recruitment and appointment; d) the provisions of the College Charters and Point Value Systems of the Colleges; e) appointment procedures of the Bureau of Vocational Education; and f) the actual practices on recruitment and appointment followed in the four educational institutions.